(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
This community service activity is motivated by the low level of digital literacy among the people of Kubu Raya Regency. Digital literacy activities aim to eliminate illiteracy and increase interest in reading and writing among people in the area. The ultimate goal is to create a society that is technologically literate and has strong reading and writing skills for the future. This activity was carried out with the concept of socialization and discussion. The material presented is related to forms of literacy movements that can be implemented in society. The socialization participants in this activity were around 20 participants at the Library Service Office. The results of this community service are in the form of a level of understanding for employees who act as the spearhead of the digital literacy drive in Kubu Raya Regency. With this service activity, the impact can be felt by participants regarding the understanding of digital literacy for the community.